Animals and animated objects in the Early Middle Ages - Gardeła, Leszek; Kajkowski, Kamil (New approaches in archaeology, 2023)
Since time immemorial, animals have played crucial roles in people?s lives. In Continental and Northern Europe, especially in the Migration Period and the Early Middle Ages, animals were both feared and revered. Varying and often ambivalent perceptions of fauna were expressed through everyday practices, religious beliefs, and the zoomorphic ornamentation of a wide plethora of objects that ranged from jewellery, weapons, and equestrian equipment to wagons and ships. This timely volume critically investigates the multivalence of animals in medieval archaeology, literature, and art in order to present human attitudes to creatures such as bears, horses, dogs, and birds in a novel and interdisciplinary way.00The chapters gathered together here explore the prominence of animals, animal parts, and their various visual representations in domestic spaces and the wider public arena, on the battlefield, and in an array of ritual practices, but also examine the importance of zoomorphic art for emerging elites at a time of social and political tensions across Scandinavia and the oft-overlooked Western Slavic and Baltic societies. This innovative book draws together scholars from across Europe in order to pave the way for a nuanced international and interdisciplinary dialogue that has the capacity to substantially increase our perception of human and animal worlds of the Early Middle Ages